THYMOMA: A RARE CAUSE OF MEDIASTINAL TUMOR IN CHILDREN - Andreea Durlan; Cristina Oana Marginean; Maria Despina Baghiu; Alina Grama; Emoke Horvath; Mihaela-Ioana Chincesan (Amaltea Medical Publishing House, 2016)
Thymoma is a thymic neoplasm composed of epithelial cells, rarely seen in children. Approximately two-thirds of mediastinal tumors in children are asymptomatic. The diagnosis is suspected following the compression of the tumor mass on the airways. We present the case of a male patient, age 7 years and 8 months, who presented at the emergency room accusing fatigue at rest or minimum effort, dry cough, intense dyspnea, orthopnea, tachypnea, chest pain, being transferred to the Pediatric Cardiology Clinic in Tirgu Mures with the following diagnoses: fluid pericarditis, right pleural effusion and cardiac tamponade. Chest computer tomography examination is carried out, describing a solid mass of 100/89/111 mm in the anterior mediastinum, partially incorporating the thymus and the vascular structures of the middle mediastinum. Pericardectomy is practiced with partial removal of the tumor and extensive tumor cytoreduction and the histopathologic examination is B3 Thymoma. Specific treatment is initiated according to the Tymoma VENUTA protocol, followed by adjuvant radiotherapy, with clinical and radiological remission. The particularity of the case is the fact that thymoma is a rare tumor on the patient's age, creating diagnostic difficulties, has no complications during treatment, with favorable evolution, with clinical and radiological remission at 1.9 years after.